1998
DOI: 10.2307/2585926
|View full text |Cite
|
Sign up to set email alerts
|

Convicting the Innocent: The Inferiority of Unanimous Jury Verdicts under Strategic Voting

Abstract: t is often suggested that requiring juries to reach a unanimous verdict reduces the probability of convicting an innocent defendant while increasing the probability of acquitting a guilty defendant. We construct a model that demonstrates how strategic voting by jurors undermines this basic intuition. We show that the unanimity rule may lead to a high probability of both kinds of error and that the probability of convicting an innocent defendant may actually increase with the size of the jury. Finally, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
457
8
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(479 citation statements)
references
References 11 publications
11
457
8
3
Order By: Relevance
“…Lim's model is a purely ideological model, which precludes the possibility of common values and dispersed information which seem central to the nature of decision-making in the court. This is a common feature of the empirical literature on voting in committees thus far, as the theory of voting with common value elements and dispersed information was developed fairly recently, following the seminal contributions of Austen-Smith and Banks (1996), and Pesendorfer (1997, 1998). 10 In this paper we follow the approach 6 More broadly, there is overwhelming evidence showing that judges are sensitive to the political environment.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Lim's model is a purely ideological model, which precludes the possibility of common values and dispersed information which seem central to the nature of decision-making in the court. This is a common feature of the empirical literature on voting in committees thus far, as the theory of voting with common value elements and dispersed information was developed fairly recently, following the seminal contributions of Austen-Smith and Banks (1996), and Pesendorfer (1997, 1998). 10 In this paper we follow the approach 6 More broadly, there is overwhelming evidence showing that judges are sensitive to the political environment.…”
Section: Related Literaturementioning
confidence: 99%
“…And because the event of being pivotal (all other n j − 1 members voting to rule in favor of the Plaintiff) here carries favorable information for the Plaintiff, in equilibrium all justices become harsher against the Defendant (so as to tilt the equilibrium inference in favor of the Defendant; see Feddersen and Pesendorfer (1998)). As a result, the move to unanimity significantly increases the probability of a mistaken decision against the Defendant (reaching a maximum of 21% for elected justices).…”
Section: Effectiveness Of Bureaucrats and Politiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…In Anlehnung an ein Computerexperiment von Guarnaschelli et al (2000), die ein rationales Entscheidungsmodell von Feddersen und Pesendorfer (1998) (Dickerson und Kemeny 2004;Gunnar et al 2009;Kirschbaum und Hellhammer 1994;Lundberg und Frankenhäuser 1980). Die exogenen Bedingungen von Stress wurden der Zeitdruck-Gruppe durch eine ablaufende Sekundenanzeige mit einem als störend empfundenen Tonsignal implementiert.…”
Section: Der Faktor Entscheidungsstressunclassified
“…15 One such real world example is the problem faced by members of a jury who would all agree upon a verdict if all uncertainty over a case were removed. 16 That work has shown that any procedure which aggregates private information, such as a jury system, may suffer from strategic, that is non-informative, voting.…”
Section: Elections Voting and Information Aggregationmentioning
confidence: 99%